In- depth investigation in the overall tax situation and its role in activating tax collection. Study case of the state directorate in Mila (2010-2019) - Boujriou, ABDERRAOUF; Harrag, MOSBAH (Milev Journal of Research and Studies, 2022)
This study aims at revealing the role of in depth investigation in the overall tax situation of people in activating and improving tax collection at the level of the state directorate in mila (2010-2019). Similarly, the taxlegislator searches for the nzczssary mechanism to contribute to incresing the tax collection and fighting tax revenue evasion that harmed the public treasury . This piece of research concluded that the overall tax situation does not effectively contribute in incresing tax collection . The study found that the amounts to be recovered were high in the majority of the years under study and reched over 80% in 2019. Hence, finding effective solutions by the tax legislator is highly required for the sake of making this kind of control more effective and helping to ameliorate tax collection.